A disputa pela legitimidade na produção cultural: o caso de Olavo de Carvalho - Olmos, Gabriel Bruno Átila Fiorotti (Universidade Federal de São Carlos, 2023)
This master's research examines the legitimization strategies employed by Olavo de Carvalho in his attempt to establish authority within the intellectual field as a professor and philosopher. We analyzed his literary works and his activity on social media, focusing on the symbolic dispute he engages in with the philosopher Marilena Chauí, a faculty member in the Philosophy Department at the University of São Paulo (USP). In addition, we collected data on the individuals most frequently mentioned by Olavo de Carvalho in order to contextualize his work. We investigated how he seeks legitimacy in cultural production, the specific strategies he employs, and the role of conservatism in shaping his intellectual formation. This study contributes to a deeper understanding of the legitimization strategies adopted by public intellectuals in the contemporary intellectual landscape.
The dispute over legitimacy in cultural production: the case of Olavo de Carvalho
La disputa por la legitimidad en la producción cultural: el caso de Olavo de Carvalho
Keywords: Olavo de Carvalho; legitimidade; produção cultural; conservadorismo; Marilena Chauí; CIENCIAS HUMANAS::CIENCIA POLITICA::TEORIA POLITICA; 4. Educação de Qualidade